Towards a Contemporary Islamic Environmental Ethics: The Nature and Moral Status of Animals = nḥū āʾḫlāqīāt bīīʾīa āʾslāmīa mʿāṣra: ṭbīʿa ālḥīūān ūmkānth ālāʾḫlāqīa - Mohamed, Nabil Yasien (Journal of Islamic ethics, 2025)
This paper examines the moral and ontological status of animals in Islamic thought and advances a contemporary Islamic environmental ethic rooted in a theocentric worldview. It critiques dominant secular models, Peter Singer’s (b. 1946) utilitarianism and Tom Regan’s (d. 2017) deontology, arguing that their one-dimensional and non-transcendental grounding limits their scope. Drawing on classical Muslim philosophers of the third/ninth to the sixth/twelfth centuries, spanning Persia to al-Andalus, this paper highlights a teleological framework that grants animals moral consideration. The Islamic ethical framework constitutes both anthropocentric and ecocentric dimensions: humans are uniquely honoured, and animals are created for human benefit (taskhīr), animals nevertheless possess sacred value, with Qurʾānic and Prophetic teachings underscoring kindness and stewardship. To reconcile the apparent anthropocentric - ecocentric impasse, a theocentric ethic is proposed, grounded in recognition of all creatures as God’s creation. We develop this ethic through a tripartite framework: (1) Divine Command Theory, (2) the Higher Objectives of the Divine Law (Maqāṣid al-Sharīʿa), and (3) Islamic Virtue Ethics. This integrative model offers a holistic, theologically grounded alternative to secular environmental ethics.